Total Suspended Load and Sediment Yield of Kayan River, Bulungan District, East Kalimantan - Dibyosaputro, Suprapto (Forum Geografi, 2005)
This research was carried out the the drainage system of Kayan river, Bulungan District, East Kalimantan. The purpose of the research were to study the physical conditions of the Kayan catchment area, calculate the suspended sediment load, and to define the total sediment yield of Kayan River. Observation method were used in this research both of direct field observation as well as laboratory observation. Data acquired in this study were include of climatic data, geology, geomorphology, soil and land cover data. Besides also rain-fall data, temperature, river discharge and suspended sediment load. The total sediment yield were calculated by mean of mathematical and statistical analysis especially of linier regression analysis. The result of the research show that total the sediment yield of Kayan River with drainage area of 6,329.452 km² is about 236,921.25 m³/km²/year. The interesting result of the statistical analysis was that the existing negative correlation between river discharge and suspended sediment load. It is the effect of the location of discharge and suspended measurement. This condition caused by sea tide effect on river discharge at the apex delta. During high tide water river trend rising up on discharge but not on suspended sediment load. Instead, also existing setting down processes takes places of the suspended sediment load into the river bottom upper stream and the apex.